The design, development, implementation and evaluation of IRISweb; A rugby-specific web-based injury surveillance system - Yeomans, C.; Kenny, I. C.; Cahalan, R.; Warrington, G. D.; Harrison, A. J.; Hayes, K.; Lyons, M.; Campbell, M. J.; Glynn, L. G.; Comyns, T. M. (Physical Therapy in Sport, 2019)
Objectives: To describe the development, implementation and evaluation of a comprehensive injury surveillance system. Design: The four phases;